The battle of the Labyrinth - Riordan, Rick (New York : Disney/Hyperion Books, 2009)
When demonic cheerleaders invade his high school, Percy Jackson hurries to Camp Half Blood, from whence he and his demigod friends set out on a quest through the Labyrinth, while the war between the Olympians and the evil Titan lord Kronos draws near.
Keywords: Mythology, Greek -- Fiction; Fantasy fiction